Wave-transmitting material and preparation method and application thereof

By using wave-transmissive materials combined with hollow glass microspheres and binder, the problem of existing materials being difficult to reduce dielectric constant and dielectric loss is solved, and a low-density and low-dielectric performance material is achieved. It is suitable for 5G radomes and meet the needs of 5G high-frequency and high-speed signal transmission.

CN119528483APending Publication Date: 2025-02-28TECHNICAL INST OF PHYSICS & CHEMISTRY - CHINESE ACAD OF SCI

Patent Information

Application Number
CN202411674079.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Existing wave-transmitting materials are difficult to further reduce dielectric constant and dielectric loss, and cannot meet the development trend of high integration of 5G technology.

Method used

Using a wave-transmissive material that combines hollow glass microspheres and binders, the hollow glass microspheres are bonded together through the binder to form a low-density wave-transmissive material, with significantly lower dielectric constant and dielectric loss.

Benefits of technology

It realizes low density, low dielectric constant and low dielectric loss wave-transmissive materials, suitable for 5G radomes, significantly reducing signal transmission losses and material density, and meeting the needs of 5G high-frequency and high-speed signal transmission.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528483A_ABST
    Figure CN119528483A_ABST
Patent Text Reader

Abstract

The invention provides a wave-transmitting material as well as a preparation method and application thereof. The wave-transmitting material comprises hollow glass microspheres and a binder, the hollow glass microspheres are bonded together through a binder located at contact points of the hollow glass microspheres, and gaps are formed among the hollow glass microspheres; the binder is at least selected from at least one of organic resin and polysaccharide biomass. The wave-transparent material disclosed by the invention has low density and low dielectric property, particularly ultralow dielectric property, good wave-transparent property, no impedance signal and light weight, and can be used in an antenna housing for 5G high-frequency high-speed communication.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wave-transmitting materials and relates to a wave-transmitting material and a preparation method and application thereof. Background Art

[0002] With the vigorous development of 5G high-frequency and high-speed technology, higher performance requirements are put forward for wave-transmitting materials, requiring them to have stable and low dielectric constant and dielectric loss performance, so as to achieve the purpose of maximum transmission and minimum loss of 5G high-frequency and high-speed signals during transmission. Since 5G millimeter waves are more prone to loss, in order to minimize the transmission loss of 5G signals at the transmitting end, the antenna cover used for 5G base stations requires high-performance wave-transmitting materials to reduce signal transmission loss. In addition, due to the requirements of industrial Internet of Things, autonomous driving, drones, VR / AR and other related terminal equipment for low signal transmission delay, high-performance wave-transmitting materials are also required to improve signal reception efficiency. Therefore, high-performance wave-transmitting materials should have lower dielectric constant and dielectric loss performance. In addition, with the increase in the complexity of the antenna system, the weight of the antenna increases, which also increases the difficulty of installation and construction and the requirements for the tower load, and antenna weight reduction becomes particularly important. The weight of the antenna cover accounts for about 20% to 35% of the total weight of the antenna. Reducing the weight of the antenna cover by reducing the material density is also the development trend of 5G antenna covers in the future. Document CN112724298A discloses a thermosetting material for preparing a high-transmittance radome and a method for preparing the radome. The dielectric constant and dielectric loss of the radome prepared using the thermosetting material are significantly reduced, the dielectric constant is reduced to 2.4-2.5, and the dielectric loss is reduced to above 0.0010. Document CN113004675A discloses a high-transmittance dielectric material for 5G millimeter wave communication. The high-transmittance dielectric material is prepared by alloying polyphenylene ether and high-impact polystyrene, adding reinforcing fillers, and obtaining a high-transmittance dielectric material. The dielectric constant (10GHz) of the wave-transmitting material is lower than 2.6, and the dielectric loss (10GHz) can be as low as 0.0016. However, it is difficult for current wave-transmitting materials to further reduce the dielectric constant and dielectric loss, and cannot meet the development trend of high integration of 5G technology. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a wave-transparent material, which has the characteristics of low density, sufficiently low dielectric constant and dielectric loss, and is particularly suitable for the field of 5G antenna cover technology.

[0004] Specifically, the present invention provides a wave-transmitting material, which includes hollow glass microspheres and a binder; the hollow glass microspheres are bonded together by the binder located at the contact points of the hollow glass microspheres, and gaps are formed between the hollow glass microspheres;

[0005] The binder is at least one selected from organic resins and polysaccharide biomass.

[0006] According to an embodiment of the present invention, in the wave-transmitting material, the mass proportion of the hollow glass microspheres is 65-99wt%, and the mass proportion of the binder is 1-35wt%. For example, the mass proportion of the hollow glass microspheres is 70-99wt% or 80-98wt%; the mass proportion of the binder is 1-30wt% or 2-20wt%.

[0007] According to an embodiment of the present invention, the hollow glass microspheres are obtained by surface modification, and the modifier is preferably a coupling agent, for example, a silane coupling agent, such as γ-aminopropyltriethoxysilane (KH550), γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560), γ-(methacryloyloxy)propyltrimethoxysilane (KH570), preferably γ-aminopropyltriethoxysilane.

[0008] According to an embodiment of the present invention, the organic resin is at least one selected from organic polymer resins such as phenolic resin, epoxy resin, polyurethane resin and silicone resin.

[0009] According to an embodiment of the present invention, the polysaccharide biomass is selected from one or more of cellulose, modified cellulose, chitosan, corn starch, modified starch (such as hydroxypropyl starch, hydroxymethyl starch), soybean starch, oxidized starch and glutinous rice starch.

[0010] According to an embodiment of the present invention, the dielectric constant (10 Hz) of the wave-transmitting material is 2.0 or less, preferably 1.8 or less, more preferably 1.5 or less, and even more preferably 1.4 or less, for example, 1.0-1.4.

[0011] According to an embodiment of the present invention, the dielectric loss (10 Hz) of the wave-transmitting material is less than 0.001, preferably less than 0.0005, and further preferably less than 0.0002, for example, 0.00015-0.0002.

[0012] According to an embodiment of the present invention, the apparent density of the wave-transmitting material is not higher than 0.5 g / cm 3 , for example 0.1-0.5 g / cm 3 .

[0013] The present invention also provides a method for preparing the above-mentioned wave-transmitting material, the method comprising:

[0014] The wave-transmitting material is prepared by mixing hollow glass microspheres, a binder, a solvent and a modifier which is optionally added or not added.

[0015] According to an embodiment of the present invention, the solvent is selected from at least one of water, ethanol, acetone, methanol, styrene, ethyl acetate and isopropanol.

[0016] According to an embodiment of the present invention, the mass ratio of the solvent to the binder is (0.5-10):1, preferably (3-8):1.

[0017] According to an embodiment of the present invention, an auxiliary agent may be further added to the method, and the auxiliary agent may be selected from one or more of a corrosion resistant agent, a waterproofing agent, a dispersant, and the like.

[0018] Preferably, the mass of the auxiliary agent is 0.1-5% of the hollow glass microspheres.

[0019] According to an embodiment of the present invention, the corrosion inhibitor is selected from one or more of calcium oxide, organosilicon, borax, boric acid, ammonium dihydrogen phosphate, urea and resin, etc. The addition of the corrosion inhibitor can also improve the water resistance and / or mildew resistance of the composite material.

[0020] According to an embodiment of the present invention, the waterproofing agent is selected from one or more of potassium methyl silicate, sodium methyl silicate, polyvinyl alcohol, acrylate, cyanate (such as isocyanate), egg white, calcium oxide, tung oil and silicone.

[0021] According to an embodiment of the present invention, the dispersant is selected from one or more of ultrafine fumed silica and polyhydroxy acid ammonium salt.

[0022] According to one embodiment of the present invention, the method comprises the following steps:

[0023] (S1) mixing a binder and a solvent to obtain a binder solution;

[0024] (S2) mixing a binder solution, hollow glass microspheres, and a modifier which is optionally added to obtain a mixed material;

[0025] (S3) introducing the mixed material obtained in step (S2) into a mold;

[0026] (S4) Drying the material of step (S3) to obtain the wave-transmitting material.

[0027] According to another embodiment of the present invention, the method comprises the following steps:

[0028] (K1) mixing a binder and a solvent to obtain a binder solution;

[0029] (K2) mixing a binder solution, hollow glass microspheres, and optionally added auxiliary agents to obtain a mixed material;

[0030] (K3) introducing the mixed material obtained in step (K2) into a mold;

[0031] (K4) Drying the material of step (K3) to obtain the wave-transmitting material.

[0032] According to an embodiment of the present invention, in step (S1) or (K1), the viscosity of the binder solution is 20 to 1500 cp, preferably 20 to 150 cp.

[0033] According to an embodiment of the present invention, in step (S2) or (K2), the mass ratio of the hollow glass microspheres to the binder is (65-99):(1-35).

[0034] According to an embodiment of the present invention, in step (S2), the amount of the modifier added is greater than 0 and less than or equal to 5 wt % of the total mass of the organic resin solution and the hollow glass microspheres.

[0035] According to an embodiment of the present invention, in step (S2) or (K2), the mixed material is kneaded to form a paste.

[0036] According to an embodiment of the present invention, in step (S4) or (K4), the drying is carried out in an electric constant temperature forced air drying oven, or natural drying.

[0037] According to an embodiment of the present invention, in step (S4) or (K4), the solvent is dried before heating and curing. For example, the solvent is dried at 30-70°C.

[0038] The temperature for heat curing is, for example, 80-250°C.

[0039] According to an embodiment of the present invention, in step (S4) or (K4), the drying process is to heat the temperature from room temperature to 30-50°C within 10-30 minutes, and keep the temperature constant for 0.5-2 hours to dry the solvent; heat the temperature from 40°C to 60-250°C within 10-30 minutes, and keep the temperature constant for 0.5-24 hours at this temperature, heat and cure, and cool naturally.

[0040] Illustratively, the temperature is raised from room temperature to 40°C within 20 minutes and maintained at 40°C for 1 hour to dry out the solvent; the temperature is raised from 40°C to 130°C within 20 minutes and maintained at 130°C for 1 hour to heat and cure the composite material, and then naturally cooled at 130°C.

[0041] The present invention also provides the application of the above-mentioned wave-transparent material in the 5G field, especially as an antenna cover for 5G high-frequency and high-speed communications.

[0042] The present invention also provides an antenna cover, which includes at least one layer of thin plate with a sandwich structure, wherein the sandwich structure sequentially includes a surface layer, a core layer and a surface layer, and the material of the core layer is the wave-transmitting material.

[0043] According to an embodiment of the present invention, the core layer is in a honeycomb or foam shape.

[0044] According to an embodiment of the present invention, the radome includes at least two layers of the thin plates having the sandwich structure.

[0045] Beneficial effects of the present invention:

[0046] The wave-transmitting material of the present invention has a low density (for example, the density of the wave-transmitting material of the present invention is 0.5 g / cm 3 Below, compared with the prior art (1g / cm 3 ) at least 50% weight reduction), low dielectric properties (such as low dielectric loss and dielectric constant), especially ultra-low dielectric properties, good wave transmission performance, no impedance to signals, and can be used in antenna covers for 5G high-frequency and high-speed communications.

[0047] The wave-transmitting material of the present invention not only has very low dielectric constant and dielectric loss in different frequency bands of high-frequency millimeter waves, but also can maintain good stability as the frequency band increases. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 is a graph showing the relationship between the dielectric constant of the wave-transmitting material of Example 1 and the frequency;

[0049] Figure 2 is a graph showing the relationship between the dielectric constant of the wave-transmitting material of Example 2 and the frequency;

[0050] Figure 3 is a graph showing the relationship between the dielectric constant of the wave-transmitting material of Example 3 and the frequency;

[0051] Figure 4 It is a schematic diagram of the structure of the thin plate in the antenna cover of the present invention, 1 is the surface layer, and 2 is the core layer. DETAILED DESCRIPTION

[0052] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0053] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0054] Example 1

[0055] Preparation of wave-transmitting material 1:

[0056] A wave-transmitting material comprises the following raw materials in parts by weight: 10 parts of organic resin, 60 parts of hollow glass microspheres, 75 parts of ethanol and silane coupling agent KH550 (accounting for 0.1wt% of the total weight).

[0057] The performance parameters of the hollow glass microspheres are as follows:

[0058] (1) True density: 0.15g / cm 3 ;

[0059] (2) Tap density: 0.1g / cm 3 ;

[0060] (3) Isostatic strength: 2MPa;

[0061] Wherein, the organic resin is a thermosetting phenolic resin, and the performance parameters are as follows:

[0062] (1) Solid content: 75%;

[0063] (2) Viscosity: 1000 cP.

[0064] The method for preparing the above-mentioned wave-transmitting material comprises the following steps:

[0065] (1) mixing the thermosetting phenolic resin and ethanol uniformly to convert the phenolic resin with higher viscosity into an ethanol solution of the phenolic resin with lower viscosity (viscosity 100 cP);

[0066] (2) mixing the alcohol solution of phenolic resin and hollow glass microspheres to form a paste, and adding KH550 accounting for 0.1 wt% of the total mass;

[0067] (3) introducing the composite cement of phenolic resin and hollow glass microspheres into a stainless steel mold for molding;

[0068] (4) Place the formed precursor in an electric constant temperature blast drying oven, raise the temperature from room temperature to 40°C within 20 minutes, and keep the temperature at 40°C for 1 hour to dry the solvent. Raise the temperature from 40°C to 60°C within 20 minutes, and keep the temperature at 60°C for 1 hour to heat and cure the composite material, and cool it naturally at 60°C.

[0069] The apparent density of the wave-transmitting material is 0.117 g / cm 3 .

[0070] Example 2

[0071] Preparation of wave-transmitting material 2:

[0072] A wave-transmitting material comprises the following raw materials in parts by weight: 10 parts of organic resin, 100 parts of hollow glass microspheres, 60 parts of isopropanol, and silane coupling agent KH550 (accounting for 0.1wt% of the total weight).

[0073] The performance parameters of the hollow glass microspheres are as follows:

[0074] (1) True density: 0.46 g / cm 3 ;

[0075] (2) Tap density: 0.30g / cm 3 ;

[0076] (3) Isostatic strength: 60MPa;

[0077] Wherein, the organic resin is a silicone resin, and the performance parameters are as follows:

[0078] (1) Solid content: 50%;

[0079] (2) Viscosity: 200 cP.

[0080] The preparation method of the composite thermal insulation material comprises the following steps:

[0081] (1) mixing the silicone resin and isopropyl alcohol evenly to convert the silicone resin with higher viscosity into an isopropyl alcohol solution of the silicone resin with lower viscosity (viscosity 50 cP);

[0082] (2) mixing the isopropanol solution of the silicone resin and the hollow glass microspheres to form a paste, and adding 0.1 wt% of KH550;

[0083] (3) introducing the composite mortar of the silicone resin and the hollow glass microspheres into a stainless steel mold for molding;

[0084] (4) Place the formed precursor in an electric constant temperature blast drying oven, raise the temperature from room temperature to 40°C within 20 minutes, and keep the temperature at 40°C for 1 hour to dry the solvent. Raise the temperature from 40°C to 220°C within 20 minutes, and keep the temperature at 220°C for 24 hours to heat and cure the composite material, and cool it naturally at 220°C.

[0085] The apparent density of the wave-transmitting material is 0.33 g / cm 3 .

[0086] Example 3

[0087] Preparation of wave-transmitting material 3:

[0088] The wave-transmitting material is made of the following raw materials in parts by weight: 3 parts of hydroxypropyl starch, 6 parts of glutinous rice starch, 75 parts of hollow glass microspheres, 20 parts of purified water, 0.1 parts of calcium oxide, 0.2 parts of isocyanate, and 0.2 parts of sodium methyl silicate.

[0089] The performance parameters of the hollow glass microspheres are as follows:

[0090] (1) True density: 0.3g / cm 3 ;

[0091] (2) Tap density: 0.2g / cm 3 ;

[0092] (3) Isostatic strength: 12 MPa;

[0093] The specific preparation steps of the wave-transmitting material are as follows:

[0094] (1) gelatinizing hydroxypropyl starch and glutinous rice starch in an appropriate amount of purified water;

[0095] (2) diluting the gelatinized mixed starch adhesive with purified water to obtain a starch glue solution;

[0096] (3) uniformly mixing the hollow glass microspheres, calcium oxide, isocyanate, sodium methyl silicate and starch glue to form a composite cement;

[0097] (4) The composite clay is introduced into a mold for molding;

[0098] (5) The formed composite clay is naturally dried and dehydrated to obtain a wave-transmitting material.

[0099] The apparent density of the wave-transmitting material is 0.225 g / cm 3 .

[0100] Test Case

[0101] Dielectric constant and dielectric loss of materials tested in Examples 1-3

[0102] The test basis for dielectric constant and dielectric loss is: SJ 20512-1995 (Test method for complex dielectric constant and complex magnetic permeability of microwave high-loss solid materials).

[0103] The test results are shown in Table 1. Figure 1-3 shown.

[0104] Example 1 Example 2 Example 3 Dielectric constant (10Hz) 1.1 1.35 1.15 Dielectric loss (10Hz) 0.00015 0.0005 0.0003

[0105] It can be seen that the density of the wave-transmitting material prepared by the present invention is low (less than 0.5 g / cm 3 , which is much lower than the prior art, such as 0.98-1.15 g / cm2 disclosed in the document CN112724298A. 3), which can have a significant weight reduction effect when used for antenna covers; in addition, the wave-transmitting material prepared by the present invention has not only very low dielectric constant and dielectric loss in different frequency bands of high-frequency millimeter waves, but also can maintain good stability as the frequency band increases, which fully meets the requirements of 5G millimeter wave communication technology for materials with low and stable dielectric constant and dielectric loss.

[0106] The above is an exemplary description of the embodiments of the present invention. However, the protection scope of the present invention is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A wave-transmitting material, characterized in that: The wave-transmitting material comprises hollow glass microspheres and a binder; the hollow glass microspheres are bonded together by the binder located at the contact points of the hollow glass microspheres, and gaps are formed between the hollow glass microspheres; The binder is at least one selected from organic resins and polysaccharide biomass.

2. The wave-transmitting material according to claim 1, characterized in that: In the wave-transmitting material, the mass proportion of the hollow glass microspheres is 65-99wt%, and the mass proportion of the binder is 1-35wt%.

3. The wave-transmitting material according to claim 1 or 2, characterized in that: The hollow glass microspheres are obtained through surface modification.

4. The wave-transmitting material according to any one of claims 1 to 3, characterized in that: The organic resin is selected from at least one of phenolic resin, epoxy resin, polyurethane resin and silicone resin; And / or, the polysaccharide biomass is selected from one or more of cellulose, modified cellulose, chitosan, corn starch, modified starch, soybean starch, oxidized starch and glutinous rice starch.

5. The wave-transmitting material according to claim 1, characterized in that: The dielectric constant (10 Hz) of the wave-transmitting material is less than 2.0; and / or, the dielectric loss (10 Hz) of the wave-transmitting material is less than 0.001; And / or, the density of the wave-transmitting material is not higher than 0.5 g / cm 3 .

6. The method for preparing the wave-transmitting material according to any one of claims 1 to 5, characterized in that: The method comprises: The wave-transmitting material is prepared by mixing hollow glass microspheres, a binder, a solvent and a modifier which is optionally added or not added.

7. The method according to claim 6, characterized in that The solvent is selected from at least one of water, ethanol, acetone, methanol, styrene, ethyl acetate and isopropanol; And / or, the mass ratio of the solvent to the binder is (0.5-10):

1.

8. The method according to claim 6 or 7, characterized in that: The method further includes adding an auxiliary agent, wherein the auxiliary agent is selected from one or more of a corrosion-resistant agent, a waterproofing agent or a dispersant.

9. Application of the wave-transmitting material according to any one of claims 1 to 5 in the 5G field. Preferably, the wave-transmitting material is used as an antenna cover for 5G high-frequency and high-speed communications.

10. A radome, characterized in that: The antenna cover includes at least one layer of thin plate with a sandwich structure, and the sandwich structure includes a surface layer, a core layer and a surface layer in sequence. The material of the core layer is the wave-transmitting material according to any one of claims 1-5.

Citation Information

Patent Citations

  • Thermosetting material for preparing high-wave-transmission radome and radome preparation method

    CN112724298A

  • High-wave-transparent dielectric material for 5G millimeter wave communication and preparation method of high-wave-transparent dielectric material

    CN113004675A

Cited By

  • Wave-transparent material, preparation method therefor, and use thereof

    WO2026108349A1